Linking the SUMO protease SENP5 to neutrophil differentiation of AML cells. Issue 1 (2015) - Federzoni, Elena A.; Gloor, Severin; Jin, Jing; Shan-Krauer, Deborah; Fey, Martin F.; Torbett, Bruce E.; Tschan, Mario P.
Abstract: In an mRNA profiling screen performed to unveil novel mechanisms of leukemogenesis, we found that the sentrin-specific protease 5 (SENP5) was significantly repressed in clinical acute myeloid leukemia when compared to healthy neutrophil samples. SENP5 is an enzyme that targets and cleaves small ubiquitin-like modifier (SUMO) residues from SUMOylated proteins. Further investigation with AML neutrophil differentiation cell models showed increased SENP5 expression upon induction of differentiation; in contrast, knocking down SENP5 resulted in significantly attenuated neutrophil differentiation. Our results support a new role of SENP5 in AML pathology, and in particular in the neutrophil differentiation of myeloid leukemic cells. Highlights: SENP5 is repressed in clinical AML when compared to healthy neutrophil samples. SENP5 expression increases during ATRA-induced differentiation of APL blasts. Knocking down SENP5 decreases ATRA-induced granulocytic differentiation. Knocking down SENP5 reduces cell viability upon differentiation.